Artificial presence, real-life influence? Effects of CGI influencers on young adults’ health behavior intentions - Saumer, Melanie; Neureiter, Ariadne; Varga, Édua Mária; Gataric, Veronika; Liu, Chelsea Yupu; Matthes, Jörg (Cyberpsychology, 2025)
Computer Generated Imagery (CGI) influencers—also known as virtual influencers—are an increasingly influential phenomenon on social media. Some CGI influencers are presented as cartoon characters and are thus clearly recognizable as non-human. Other CGI influencers, however, are almost indistinguishable from real humans. Although CGIs can elicit parasocial interaction (PSI), we lack research distinguishing cartoon-look CGI influencers from human-look CGI influencers. Also, we do not know whether CGIs can lead to persuasive effects. This is particularly relevant regarding health topics because CGIs cannot have health issues. In an experimental study with a quota-based sample of N = 443 young adults (62.8% female) aged 16 to 26 from the United Kingdom, we compared the effects of a real human influencer, a human-look CGI influencer, and a cartoon-look CGI influencer advising about insomnia (i.e., sleeping problems) on young adults’ PSI and health behavior intentions. We found that PSI was strongest for the real human and weakest for the cartoon-look CGI influencer and was significantly positively related to young adults’ health behavior intentions. Personal affectedness by insomnia and gender did not moderate these relationships. Overall, findings suggest that the persuasive power of CGIs is limited, at least regarding topics such as health. Implications are discussed.